Effective anti-doping testing program during major sport events: a comparative analysis of two multi-sport tournaments held in Poland in 2017 and 2023 - Lipska, Elżbieta; Szamotulska, Katarzyna; Kwiatkowska, Dorota; Rynkowski, Michał (Frontiers in Sports and Active Living, 2025)
IntroductionMajor Sporting Events (MSEs), particularly Multi-Sport Tournaments (MSTs), present significant logistical and operational challenges in the implementation of effective Anti-Doping Programs (ADPs). This study presents a comparative analysis of ADP implementation during two MSTs hosted in Poland: The World Games 2017 (TWG 2017) and the European Games 2023 (EG 2023).MethodsThe analysis encompasses organizational logistics, sample collection processes, laboratory testing, and the broader implications for national anti-doping activities conducted by the Polish Anti-Doping Agency (POLADA) and the Polish Anti-Doping Laboratory (PLAD), which in 2017 operated under the name Department of Anti-Doping Research at the Institute of Sport.ResultsTWG 2017 involved 3,292 athletes, whereas EG 2023 hosted 6,380 participants. Although both events utilized the same number of sport venues, the wider geographical distribution of EG 2023 introduced greater logistical complexity. The number of Sample Collection Personnel (SCP) increased in absolute terms for EG 2023, comprising 90 Doping Control Officers (DCO) and 120 chaperones, in contrast to 37 DCOs and 35 chaperones during TWG 2017. However, when adjusted to the number of athletes, the increase was not statistically significant. This rise in SCP corresponded to a significant increase in testing volume: 1,210 samples were collected at EG 2023 compared to 401 at TWG 2017, with a notably higher proportion of out-of-competition tests. Both MSTs placed considerable demands on the routine operations of POLADA and PLAD.DiscussionDespite structural similarities and the involvement of shared institutional stakeholders, EG 2023 represented a significant scale-up in ADP due to the increased number of athletes, greater geographical dispersion, and enhanced testing complexity. These findings underscore the necessity for scalable, context-specific and coordinated anti-doping strategies. These need to be tailored to the unique operational demands of MSTs, distinguishing them from single-sport events.